Cell Death Pathways as Therapeutic Targets in Rhabdomyosarcoma. (12th January 2012) - Fulda, Simone
Abstract : Resistance of rhabdomyosarcoma to current therapies remains one of the key issues in pediatric oncology. Since the success of most cytotoxic therapies in the treatment of cancer, for example, chemotherapy, depends on intact signaling pathways that mediate programmed cell death (apoptosis), defects in apoptosis programs in cancer cells may result in resistance. Evasion of apoptosis in rhabdomyosarcoma may be caused by defects in the expression or function of critical mediators of apoptosis or in aberrant expression of antiapoptotic proteins. Therefore, the identification of the molecular mechanisms that confer primary or acquired resistance to apoptosis in rhabdomyosarcoma presents a critical step for the rational development of molecular targeted drugs. This approach will likely open novel perspectives for the treatment of rhabdomyosarcoma.